Confirmation of Sex of Domestic Ruminants by Using Duplex PCR - Bhole, P. D.; Charjan, Rupali; Banubakode, S. B.; Nandeshwar, N. C.; Mainde, U. P.; Singh, Anand; Boddupalli, Ayesha (Indian Journal of Veterinary Anatomy, 2023)
The present work was carried out on blood samples collected from domestic ruminants viz. cattle, buffalo, sheep, and goat. The DNA extracted from blood samples was subjected separately for PCR by using the SRY gene and GAPDH and also by duplex PCR by using SRY and GAPDH together as biological markers. The amplicon was loaded separately in three different 2% agarose gels and run under gel electrophoresis. The simplex PCR of the SRY gene showed a band at 122 bp only for male animals, while the simplex PCR of GAPDH exhibited a single band at 218 bp for males as well as females. The results obtained were cross-verified and confirmed by conducting duplex PCR, which showed a double band at 122bp & 218bp for males and a single band only at 2l 8bp for females.